SCIENCE E-MODULE BASED ON LOCAL WISDOM TO IMPROVE SCIENTIFIC LITERACY AND CRITICAL THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Mardiana, Alif; Waluyo, Joko; Aristya Putra, Pramudya Dwi (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
One of the skills that needs to be equipped to prepare a quality generation that meets the criteria of the 21st century is scientific literacy skills and high-level thinking skills, including thinking skills. Scientific literacy skills and critical thinking skills in students can be built through local wisdom which is used as a learning resource. The use of teaching materials in the form of e-modules can encourage students to learn more actively. The aim of this research is to produce a science e-module based on local wisdom to improve scientific literacy and valid critical thinking skills of junior high school students.  The method used is of the research and development type by adapting the 4D model developed by Thiagarajan. In the 4D model there are 4, namely definition, design, development and dissemination.  The validation results which included aspects of content suitability, presentation aspects, language aspects, graphic aspects by three validators obtained an average percentage of 93% with a very valid category. This shows that the e-module that has been developed has the qualifications to be suitable for use.